ID 270 – Nerve ultrasound findings in cmt neuropathy. Issue 3 (March 2016) - Padua, L.; Pazzaglia, C.; Coraci, D.; Lucchetta, M.; Paolasso, I.; Granata, G.; Cacciavillani, M.; Luigetti, M.; Manganelli, F.; Pareyson, D.; Briani, C.
Abstract : We have extensively evaluated nerve ultrasound (US) pattern in different CMT subgroup patients, assessing median, ulnar, fibular, tibial, sural nerves pattern. Sixty-nine patients affected with hereditary neuropathy (including 16 CMT1A, 4 CMT1B, 3 CMT1C, 2 CMT1D, 4 CMT1 not defined, 22 CMT2, 8 CMTX, 10 HNPP) underwent widespread nerve US evaluation. Nerve cross sectional area (CSA) and echotexture were evaluated at four limbs in different sites, both distally and proximally. Data were correlated with age and clinical pictures. Nerve CSA seems to be dependent on the following variables: CMT type, age and site. In particular CSA is very smaller in CMT2 type and larger in the middle aged subjects. Moreover, nerve size appears bigger in the proximal sites. Nerve US evaluation may play a supportive role in the diagnostic process in patients with hereditary neuropathies and poor clinical picture or inconclusive neurophysiological findings. Besides, the extension of US evaluation also to proximal nerve segments helped widen our knowledge in the pathomechanism of the disease.